Achieving enhanced energy storage performance and ultra-fast discharge time in tungsten–bronze ceramic - Yuejun Dan; Liupan Tang; Wenzhi Ning; Yingzhi Meng; Changzheng Hu; Laijun Liu; Liang Fang (Journal of Advanced Ceramics, 2024)
The rapid development of capacitors with high energy density and efficiency has been driven by advanced electronic systems and innovative pulsed power applications. In this study, we prepared Sr4.5−xBaxSm0.5Zr0.5Nb9.5O30 (x = 2.5, 3, 3.5, 4, 4.5) dielectric ceramics, which exhibited structural distortion due to the co-occupation of Ba2+, Sr2+, and Sm3+ in the A-site and the partial substitution of Nb5+ by Zr4+ in the B-site. The ordered/disordered distribution due to these distortions thus generated polar nanoregions (PNRs) and induced a relaxation ferroelectric behavior, which was verified by the high-resolution transmission electron microscopy. Through the use of the Vogel–Fulcher and Maxwell–Boltzmann equations, we found that easy inversion and small dipole sizes are crucial for achieving high energy storage density and efficiency. The Sr4.5−xBaxSm0.5Zr0.5Nb9.5O30 (x = 3.5) dielectric ceramic displayed a ferroelectric/paraelectric transition near room temperature. Subsequent ferroelectric testing revealed large energy storage density (Wrec = 4.31 J·cm−3) and high efficiency (η = 93.8%) at 310 kV·cm−1. Furthermore, Sr4.5−xBaxSm0.5Zr0.5Nb9.5O30 (x = 4.5) exhibited higher breakdown field strength due to its large resistivity and small grain size. This led to energy storage density of approximately 5.3 J·cm−3 at 460 kV·cm−1. Additionally, Sr4.5−xBaxSm0.5Zr0.5Nb9.5O30 (x = 3.5) demonstrated current density (CD) of approximately 713.38 A·cm−2 and power density (PD) of approximately 87.51 MW·cm−3, with ultrafast discharge time of 34 ns and excellent discharge energy density (Wdis) of approximately 2.27 J·cm−3. Overall, this study presents a promising approach for developing dielectric ceramic materials that hold potential for applications in innovative pulsed power components.